The Bath University rugby shuttle test (BURST): A pilot study - Roberts, S.; Stokes, K.; Weston, L.; Trewartha, G. (International Journal of Sports Physiology and Performance, 2010)
Purpose. This study presents an exercise protocol utilizing movement patterns specific to rugby union forward and assesses the reproducibility of scores from this test. Methods. After habituation, eight participants (mean ± SD: age = 21 ± 3 y, height = 180 ± 4 cm, body mass = 83.9 ± 3.9 kg) performed the Bath University Rugby Shuttle Test (BURST) on two occasions, 1 wk apart. The protocol comprised 16 × 315-s cycles (4 × 21-min blocks) of 20-m shuttles of walking and cruising with 10-m jogs, with simulated scrummaging, rucking, or mauling exercises and standing rests. In the last minute of every 315-s cycle, a timed Performance Test was carried out, involving carrying a tackle bag and an agility sprint with a ball, followed by a 25-s recovery and a 15-m sprint. Results. Participants traveled 7078 m, spending 79.8 and 20.2% of time in low- and high-intensity activity, respectively. The coefficients of variation (CV) between trials 1 and 2 for mean time on the Performance Test (17.78 ± 0.71 vs 17.58 ± 0.79 s) and 15-m sprint (2.69 ± 0.15 vs 2.69 ± 0.15 s) were 1.3 and 0.9%, respectively. There was a CV of 2.2% between trials 1 and 2 for mean heart rate (160 ± 5 vs 158 ± 5 beats/min) and 14.4% for blood lactate (4.41 ± 1.22 vs 4.68 ± 1.68 mmol/L). Conclusion. Results suggest that measures of rugby union-specific high-intensity exercise performed during the BURST were reproducible over two trials in habituated participants.